Interplay between the catabolite repression control protein Crc, Hfq and RNA in Hfq-dependent translational regulation in Pseudomonas aeruginosa. Issue 3 (13th December 2017) - Sonnleitner, Elisabeth; Wulf, Alexander; Campagne, Sébastien; Pei, Xue-Yuan; Wolfinger, Michael T; Forlani, Giada; Prindl, Konstantin; Abdou, Laetitia; Resch, Armin; Allain, Frederic H -T; Luisi, Ben F; Urlaub, Henning; et al.
Abstract: In Pseudomonas aeruginosa the RNA chaperone Hfq and the c atabolite r epression c ontrol protein (Crc) act as post-transcriptional regulators during carbon catabolite repression (CCR). In this regard Crc is required for full-fledged Hfq-mediated translational repression of catabolic genes. RNAseq based transcriptome analyses revealed a significant overlap between the Crc and Hfq regulons, which in conjunction with genetic data supported a concerted action of both proteins. Biochemical and biophysical approaches further suggest that Crc and Hfq form an assembly in the presence of RNAs containing A-rich motifs, and that Crc interacts with both, Hfq and RNA. Through these interactions, Crc enhances the stability of Hfq/Crc/RNA complexes, which can explain its facilitating role in Hfq-mediated translational repression. Hence, these studies revealed for the first time insights into how an interacting protein can modulate Hfq function. Moreover, Crc is shown to interfere with binding of a regulatory RNA to Hfq, which bears implications for riboregulation. These results are discussed in terms of a working model, wherein Crc prioritizes the function of Hfq toward utilization of favored carbon sources.